1991
DOI: 10.1177/00220345910700091401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Beta-adrenergic Blocking Agent on Dental Anxiety

Abstract: The effect of propranolol was studied on 23 dental phobics in a double-blind, placebo-controlled clinical trial involving actual dental treatment. The subjects were selected because they showed high physiological reactivity in the dental situation. Twelve subjects received the test drug and 11 subjects received the placebo at individualized doses of either 80 or 120 mg. A significant difference in self-reported anxiety at the injection phase of treatment and less overall pain intensity and aversiveness were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
0
20
1
1
Order By: Relevance
“…Propranolol successfully reduced anxiety in dental phobics (38), and avoidance behavior in panic disorder patients (39). Other studies, however, showed no effect of propranolol on subjective anxiety in phobics (40), or expression of cued fear conditioning (7).…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol successfully reduced anxiety in dental phobics (38), and avoidance behavior in panic disorder patients (39). Other studies, however, showed no effect of propranolol on subjective anxiety in phobics (40), or expression of cued fear conditioning (7).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, propranolol and other b-adrenergic antagonists have been shown to reduce anxiety provoked by stressful situations (Liu et al, 1991;Dyck and Chung, 1991;Laverdure and Boulenger, 1991) or drug withdrawal (Bailly et al, 1992). These compounds are primarily effective in reducing moderate, but not extreme, autonomic somatic symptoms of anxiety (Tyrer, 1988).…”
Section: Predictive Validitymentioning
confidence: 99%
“…As far as we know, the present study is the first to investigate the effect of propranolol for critically ill patients. Previous studies mentioned above have shown the effects of propranolol on various neurocognitive disorders besides hyperactive delirium, and some of these are associated with delirium in the ICU (16, 19, 20). Therefore, treatment of these conditions may lead to a decrease in the incidence of delirium in the ICU (1, 30).…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al conducted a small randomized controlled trial ( n  = 15) in which they administered either propranolol or placebo 1 h prior to a dental procedure. Patients who received propranolol reported lower pain and anxiety scores on a visual analog scale before, during and after the procedure (16). Vaiva et al were able to reduce the incidence of PTSD symptoms using propranolol in a small ( n  = 19) non-randomized study of trauma patients (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation